To the Landau theory of relaxation phenomena in plasma - Sokolovsky, A.I.; Gorev, V.N.; Chelbaevsky, Z.Yu. (Вопросы атомной науки и техники, 2012)
The distribution function of quasi-equilibrium plasma in linear approximation in differences of temperatures and velocities of its components has been obtained. It was done on the basis of our generalization of the Chapman-Enskog method. It is found that the Maxwell distribution with different velocities and temperatures of components is not a true nonequilibrium distribution function even in the linear approximation. The Landau theory of relaxation phenomena in plasma gives a leading approximation of the developed theory. It was established that relaxation takes place in the case of small difference between temperatures and velocities of components regardless of the mass ratio. Получена функция распределения квазиравновесной плазмы в линейном приближении по разностям температур и скоростей её компонент. Это сделано на основе нашего обобщения метода Чепмена-Энскога. Найдено, что распределение Максвелла с различными скоростями и температурами компонент не является истинной неравновесной функцией распределения даже в линейном приближении. Теория Ландау релаксационных явлений в плазме дает главное приближение развитой теории. Установлено, что релаксация имеет место в случае малой разности между температурами и скоростями компонент независимо от отношения масс частиц. Одержано функцію розподілу квазірівноважної плазми в лінійному наближенні за різницями температур і швидкостей її компонент. Це зроблено на основі нашого узагальнення методу Чепмена-Енскога. Знайдено, що розподіл Максвелла з різними швидкостями і температурами компонент не є істинна нерівноважна функція розподілу навіть у лінійному наближенні. Теорія Ландау релаксаційних явищ у плазмі дає головне наближення розвинутої теорії. Встановлено, що релаксація має місце у випадку малої різниці між температурами і швидкостями компонент незалежно від відношення мас частинок.